2019
DOI: 10.1249/mss.0000000000002047
|View full text |Cite
|
Sign up to set email alerts
|

Activity Intensity, Volume, and Norms: Utility and Interpretation of Accelerometer Metrics

Abstract: The physical activity profile can be described from accelerometer data using two population-independent metrics: average acceleration (ACC, volume) and intensity gradient (IG, intensity). This paper aims to: 1) demonstrate how these metrics can be used to investigate the relative contributions of volume and intensity of physical activity for a range of health markers across datasets; and 2) illustrate the future potential of the metrics for generation of age and sexspecific percentile norms. Methods: Secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 25 publications
6
74
0
Order By: Relevance
“…MX is a novel accelerometer metric that captures the intensity (acceleration) during a person's most active period of the day. 30 In addition, we report the intensity gradient, which reflects the distribution of physical activity intensity across the 24 hour day and has been described in detail elsewhere. 31 In brief, it describes the negative curvilinear relationship between physical activity intensity and the time accumulated at that intensity during the 24 hour day.…”
Section: Chronotypementioning
confidence: 99%
“…MX is a novel accelerometer metric that captures the intensity (acceleration) during a person's most active period of the day. 30 In addition, we report the intensity gradient, which reflects the distribution of physical activity intensity across the 24 hour day and has been described in detail elsewhere. 31 In brief, it describes the negative curvilinear relationship between physical activity intensity and the time accumulated at that intensity during the 24 hour day.…”
Section: Chronotypementioning
confidence: 99%
“…[12, 13]) or intensity and volume may have a cumulative effect (e.g. [14]). Two data-driven metrics that, together, capture the volume and intensity of physical activity of the 24-h activity profile are the average acceleration (indicative of volume) and the intensity gradient (intensity distribution) [15].…”
Section: Main Textmentioning
confidence: 99%
“…Together, the average acceleration and the intensity gradient enable investigation into whether the volume and intensity of physical activity have independent, additive or interactive effects on health. Using these metrics, we have recently shown that the intensity gradient was independently associated with body fatness, metabolic risk and cardiorespiratory fitness in children [14, 16]; intensity and volume were additively associated with body fat in adults; and adult bone health was highest if activity intensity was high, somewhat irrespective of volume [14].…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations